Artificial Intelligence and Tarannum Pedagogy: Towards an Ethical Islamic Framework for Ecological and Social Justice - Ramli, Mohd Shahidan; Sahad, Mohd Nizam; Mohd Din, Khairil Fikri (Unisia, 2025)
The integration of artificial intelligence (AI) into Islamic education has gained increasing scholarly attention, particularly in Qur’anic pedagogy. Among its dimensions, Tarannum the melodic art of Qur’anic recitation remains understudied in digital contexts despite its vital role in preserving cultural and spiritual heritage. This systematic literature review (SLR) investigates how AI can be applied to support Tarannum pedagogy while ensuring alignment with Islamic ethics, ecological awareness, and social justice. The article addresses two main objectives: first, to analyse how Tarannum can be preserved and enhanced through AI-based learning tools while remaining consistent with Islamic pedagogical principles; and second, to propose an ethical Islamic framework for AI-enabled Tarannum pedagogy grounded in maqāṣid al-sharī‘ah, trusteeship ethics, and principles of sustainability. The review follows the PRISMA protocol and systematically synthesises thirty nine peer reviewed articles published between 2010 and 2025. Data sources included Scopus, Web of Science, Google Scholar and ERIC with studies screened and categorised into four main themes: (1) AI in Qur’anic recitation and tajwīd learning, (2) Tarannum as cultural and pedagogical heritage, (3) Islamic ethics and AI governance, and (4) ecology and social justice in Islamic pedagogy. Findings show that while AI systems achieve high accuracy in tajwīd error detection and recitation recognition, Tarannum’s spiritual and aesthetic dimensions remain largely neglected in digital pedagogy. Islamic ethical frameworks provide strong conceptual guidance but require practical operationalisation. Moreover, ecological and social justice discourses are rarely connected to Tarannum education. This review concludes that a comprehensive framework integrating AI, Tarannum pedagogy, Islamic ethics, and sustainability is essential for advancing Qur’anic education that is both technologically innovative and spiritually authentic.